Applying psychology to early child development - Flanagan, Cara, 1951- (London : Hodder & Stoughton, 1996)
This book looks at how psychological knowledge and methods can be applied to the issues surrounding early child development. In a lively and accessible style, it makes numerous connections between theory, practice and everyday experience.
Includes bibliographical references (p. 174-185) and index.
Keywords: Child psychology; Child development -- Psychological aspects; Child Care